Globalization: Theory and Practice by Eleonore Kofman and Gillian Youngs, editors. Pinter: 1996. xii + 339 pp. (American Journal of Islam and Society, 1998)
Globalization is a subject about which it is very easy to write copiously and badly.This is inevitable, given its literal implication of change in everything humanity holdsdear, thereby eluding encapsulation within any single paradigm, theory, or perspective.Legions of authors, however, not deterred by this fact have elaborated on their uniquelytrue reading of the outcomes of this phenomenon, so many carefully avoiding serious criticismof the idea in so doing. Now, as the millenium nears, whole populations are certainin their knowledge that globalization is here, but very few individuals can claim crediblyto know what it is, how it works, and where it will take us.One useful approach to doing justice to so broad a topic within a single volume is toengage the services of several authors, each dealing with those facets of globalization forwhich they are best equipped. This is the approach taken in the work under review, wherethe talents of 23 individuals have been pooled. The downside is the risk that no tangibleconcept of globalization will emerge from the various contributions and that the readerwill be left unconvinced that so many disparate treatments describe the same subject.Editors Kofman and Youngs exhibit some sensitivity to this problem and, to theircredit, designed their book to encompass a sizable part of the intellectual territory of globalization.From the vantage points of geography, politics, and international relations, aswell as sociology, law, and even epistemology, each author shares his or her view of globalizationin action. If, at times, the view is from quite a distance or obstructed by foregroundissues of only indirect importance, this is compensated for by the novelty of theperspectives offered. As far as intellectual coverage is concerned, a stronger economiccontent is notable by its absence, for although economists have their say on the subjectnearly everywhere else, the intimacy between politics and economics (as opposed to capitalism)in the context of globalization deserves every attention.Kofman and Youngs are anxious to position this work as part of the “second wave”of serious and scholarly research on globalization, although in so doing they tend toassume that the “first wave” (presumably consisting of descriptive or historical narratives)yielded a solid enough foundation on which to build. The fact remains that thevery hypothesis of globalization has its detractors, and in their introduction, the editorsfail to convince the critical reader of globalization’s conceptual or empirical validity.Similarly, several later chapters could easily be rewritten without recourse to “the Gword,” for they are more useful as perspectives on postlmodernism, capitalism,interhationalism, internationalization, or regionalism, to name only a representativeselection. Although many participants in academic discourse comprehend globalizationin its particular manifestations, others, myself included, prefer that its elaboration on aholistic level should be featured just as often. The tendency to work within the “globalizationof ...” framework, rather than “globalization is ...,” eventually may obscurevital truths of the same variety as a failure to see the forest shrinking due to focusedinterest in the growth of individual trees. A book such as this should, by its close, clarifywhat globalization is not, in order to demonstrate the theory’s tractability. Thiswould serve the additional purpose of countering those who write globalization off asfantasy, or worse, as a conspiracy to revive the fortunes of authors exhausted on otherintellectual fronts. Unfortunately, despite its ostensible commitment to the “is”approach, a good deal of Globalizution is intent on describing the more readily circumscribedincidents of an ineffable force ...